Sistema de información para el registro y gestión de vendedores informales de los municipios de Colombia (2021)
The objective of this work is to carry out the analysis, design and implementation of an application that allows the registration and management of the basic information of informal vendors in the municipalities of Colombia, taking as a reference what is proposed in the public policy of informal vendors.